Implant and spinal mobility influence on the spinal curvature correction in adolescent idiopathic Lenke I type scoliosis - Bernotavičius, Giedrius; Saniukas, Kęstutis; Vaičiulėnaitė, Justina; Sabaliauskas, Vykintas (Lietuvos chirurgija, 2015)
Background and objectiveThere are still a few researches accomplished to evaluate the advantages and disadvantages of screw, hybrid, and hook techniques in the treatment of adolescent idiopathic scoliosis. As the results are controversial, researchers still look for optimally safe, least traumatizing and economically reasonable methods to treat spinal deformities. The aim of this study is to analyze postoperative spine deformity correction results for Lenke type 1 dependent on fixation type and preoperative bending films.Patients and methodsA retrospective study was performed. Patients admitted to the Children’s Hospital, Affiliate of Vilnius University Hospital Santariskiu Klinikos Orthopedic Department in the period of 1994–2013 were included; 74 cases were analyzed. Three groups according to spine implants were generated. The first included patients treated with pedicle screw fixation, the second – hybrid, and the third – hook fixation. Inclusion criteria: the adolescent age group (10–18), idiopathic scoliosis Lenke I type who undergone posterior spinal fusion with pedicle screws; hybrid fixation and hook application were evaluated in order to compare curve correction dependence on fixation type and curve flexibility. Thoracic and lumbar curve measurements on the coronal plane were performed using the Cobb technique applied on anterior posterior radiographs taken before and two days after surgery. Also, to measure curve flexibility, preoperative passive standing bending films were analyzed. Curve degrees in preoperative passive bending films were compared with the remaining postoperative spinal curves in groups separately. The remaining postoperative curves were compared respectively. ResultsIn total, 74 cases met the inclusion criteria, of them 67 (90.50%) girls and 7 (9.50%) boys. The mean preoperative thoracic Cobb angle was 51.07º (±6.20) in the screw group, 52.88º (±7.26) in the hybrid and 55.45º (±10.94) in the hook group. To compare the preoperative stiffness of the curves, the flexibility % was calculated, with no difference in the groups (p > 0.05). The mean postoperative thoracic Cobb curve angle was 15.81º (±5.28), 21.63º (±6.89), and 27.55º (±8.25), respectively. The mean correction of the thoracic curve was 68.87% in the screw group, 58.76% in the hybrid and 50.27% in the hook group. The mean preoperative lumbar curve Cobb angle was 32.07º (±5.73) in the screw group, 32.50º (±12.33) in the hybrid and 34.74º (±7.50) in the hook group. The mean postoperative lumbar curve Cobb angle was 7.59º (±6.63), 10.94º (±7.52), and 16.06º (±6.89), respectively. The mean correction of the lumbar curve was 75.58% in the screw group, 66.27% in the hybrid and 53.53% in the hook group. The fixation level according to groups: screw Th4-L1, hybrid Th3-L3, hook Th3-L3. ConclusionsThe thoracic curve tends to recover more than the curve remaining in the lateral bending film. Only screw fixation is able to correct the lumbar curve for the Lenke type 1 as it is expected in the remaining lateral bending curve. Thoracic and lumbar deformity using screw fixation recovers on the average by 20% more than hook and by 10% more than hybrid application. The pedicular screw construct is shorter and is able to correct the thoracic curve whatever the modifier type (A, B or C); however, the lumbar curve correction drops when the modifier type is B or C. The other operative methods are less effective to correct both thoracic and lumbar curves whatever the modifier type and also tend to lose the correction % for types 1B or 1C.
Keywords: adolescent idiopathic scoliosis; pedicular screws; hook fixation; hybrid fixation; bending X-rays; flexibility